Epidemiological situation of COVID-19 in South America - Echeverría Ibazeta, R. Rainer (2020)
Currently the coronavirus (COVID-19) infection has become a public health problem worldwide. In December 2019, in the city of Wuhan, province of Hubei, China, the first cases of pneumonia of unknown etiology were reported, which incremented rapidly in other provinces of the country. Subsequently, SARS-CoV2 was identified as the causal agent and in mid-January 2020, the World Health Organization (WHO) reported over 280 confirmed cases of COVID-19 in China, Thailand, Japan and Korea. In South America, the first case of COVID-19 is made known on February 26, 2020 in the city of Sao Paulo, Brazil, identified as a male patient of 61 years of age from the region of Lombardy in Italy. Soon after there were other confirmed cases imported from the Asian and European continents in other south American countries.